Features of Grooved Ceramic in Some Crusader Castles in the Levantine Coast During the Mamluk Period (Damascus University Journal of Historical Studies, 2022)
The research was interested in studying one of the most important ceramic manufacturing techniques during the Islamic ages. It is the technology of making grooved ceramic wares (sgraffito), implemented on two types of dishes, so to speak, they are great bowls and bowls of different scales in order to identify the quality of the clay used in its manufacture, and how to burn them in the ovens, and the pattern of plant and geometric decorations applied to their surface, and coloring these decorations with various color oxides.The research was based on the descriptive and analytical study of grooved wares dating back to the Mamluk period and discovered in the castles of the Crusader Levantine Coast, and focus on the wares castles of Al-Marqab and Salah al-Din as a template of study, and compare the studied wares with each other, to identify the common features of this technique and find out the points of difference between them.
Keywords: grooved ceramic; sgraffito; al-Marqab; Salah al-Din